Application of cloud computing solutions in enterprises. Review of selected foreign practical applications - Nowicki, Adam; Ziora, Leszek (Zastosowanie rozwiązań cloud computing w przedsiębiorstwach. Przegląd wybranych zagranicznych zastosowań praktycznych, 2011)
The article is focused on the issues of cloud computing solutions. It presents characteristics of cloud computing, its deployment models, fundamental architecture elements creating such a solution, proposal of Cloud-Based model for Business Organizations including virtualization. It also presents foreign practical application of cloud computing solutions provided in such enterprises as Microsoft, Google, Amazon. These enterprises are vendors of such solutions as well
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 203-213
Keywords: cloud computing; Software as a Service; grid computing